Pharmacokinetics of levosimendan in critically Ill children on extracorporeal membrane oxygenation: a prospective observational study - Bertin, Stéphane; Haefliger, David; Perez, Maria-Helena; Guidi, Monia; Decosterd, Laurent A.; Chanez, Vivianne; Di Paolo, Ermindo R.; Buclin, Thierry; Livio, Françoise (Frontiers in Pediatrics, 2025)
BackgroundLevosimendan is used off-label in pediatrics and pharmacokinetic (PK) data in this population are scarce. The only study in critically ill patients on extracorporeal membrane oxygenation (ECMO) showed altered PK parameters. Our study aimed to characterize the PK profile of levosimendan and its metabolites in critically ill children on ECMO and assess the adequacy of current dosing practices.MethodsWe conducted a prospective observational PK study in a Swiss tertiary pediatric intensive care unit. Children on ECMO for hemodynamic failure receiving continuous levosimendan infusion (0.1 µg/kg/min for 48 h) were included.ResultsFive full-term newborns and one infant were included (median age 24 days). A total of seven sets of eight blood samples were collected. Median (range) steady-state levosimendan concentration was 16.68 (7.92–18.88) ng/ml. Non-compartmental analysis revealed a median clearance (CL) of 5.99 (5.18–11.32) ml/min/kg, volume of distribution (Vd) of 1.48 (1.07–6.27) L/kg, and elimination half-life of 4.59 (3.40–6.50) hours. ECMO and body composition of our patients, mostly post-cardiac surgery neonates, might explain the increased CL and Vd in our population compared to older children not on ECMO (CL 3.60 ml/min/kg, Vd 0.35 L/kg). Active metabolite OR-1896 concentrations were markedly lower than in neonates not on ECMO.ConclusionsIn our cohort of critically ill children on ECMO, augmented CL and Vd were associated with low levosimendan concentrations. This suggests that dosage should be increased in this context, to achieve optimal exposure of levosimendan and its active metabolite.